2017
DOI: 10.1177/0394632017707610
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and benefit of a tetramethoxyluteolin-containing skin lotion

Abstract: As many as 40% of people have sensitive skin and at least half of them suffer from pruritus associated with allergies, atopic dermatitis (AD), chronic urticaria (CU), cutaneous mastocytosis (CM), and psoriasis. Unfortunately, the available topical formulations contain antihistamines that are often not as effective as those containing corticosteroids. Certain natural flavonoids have anti-inflammatory actions. We recently reported that the natural flavonoid tetramethoxyluteolin has potent antiallergic and anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…We have shown that methoxyluteolin is a more potent inhibitor of human mast cells (57) and human keratinocytes (37) compared with luteolin, and that therapeutic doses can be achieved in vivo (Table S1). Flavonoids (58), particularly luteolin (59) and methoxyluteolin (60), are considered safe. The time course of the key signaling steps of stimulation with the combination of IL-33 and SP led to JNK kinase activation within the first 5 min, whereas IKβ-α became active within the first hour, and both remained active over the next 4 h of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that methoxyluteolin is a more potent inhibitor of human mast cells (57) and human keratinocytes (37) compared with luteolin, and that therapeutic doses can be achieved in vivo (Table S1). Flavonoids (58), particularly luteolin (59) and methoxyluteolin (60), are considered safe. The time course of the key signaling steps of stimulation with the combination of IL-33 and SP led to JNK kinase activation within the first 5 min, whereas IKβ-α became active within the first hour, and both remained active over the next 4 h of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, methlut is also metabolically more stable than lut . A methlut‐containing skin lotion is now commercially available and showed benefit in mild psoriasis …”
Section: Discussionmentioning
confidence: 99%
“…The ability of the natural flavonoid tetramethoxyluteolin to inhibit mast cells stimulated by either IL-33, substance P, or their combination (2), which we report in our paper, has now been validated in a pilot clinical trial: a skin lotion containing tetramethoxyluteolin was shown to reduce skin inflammation in patients with atopic dermatitis and psoriasis (10).…”
mentioning
confidence: 86%